Selection of nectar plants for use in ecological engineering to promote biological control of rice pests by the predatory bug, Cyrtorhinus lividipennis, (Heteroptera: Miridae) - Zhu, Pingyang; Lu, Zhongxian; Heong, Kong Luen; Chen, Guihua; Zheng, Xusong; Xu, Hongxing; Yang, Yajun; Nicol, Helen I.; Gurr, Geoff M. (Public Library of Science, 2014)
Ecological engineering for pest management involves the identification of optimal forms of botanical diversity to incorporate into a farming system to suppress pests, by promoting their natural enemies. Whilst this approach has been extensively researched in many temperate crop systems, much less has been done for rice. This paper reports the influence of various plant species on the performance of a key natural enemy of rice planthopper pests, the predatory mirid bug, Cyrtorhinus lividipennis. Survival of adult males and females was increased by the presence of flowering Tagetes erecta, Trida procumbens, Emilia sonchifolia (Compositae), and Sesamum indicum (Pedaliaceae) compared with water or nil controls. All flower treatments resulted in increased consumption of brown plant hopper, Nilaparvata lugens, and for female C. lividipennis, S. indicum was the most favorable. A separate study with a wider range of plant species and varying densities of prey eggs showed that S. indicum most strongly promoted predation by C. lividipennis. Reflecting this, S. indicum gave a relatively high rate of prey search and low prey handling time. On this basis, S. indicum was selected for more detailed studies to check if its potential incorporation into the farming system would not inadvertently benefit Cnaphalocrocis medinalis and Marasmia patnalis, serious Lepidoptera pests of rice. Adult longevity and fecundity of both pests was comparable for S. indicum and water treatments and significantly lower than the honey solution treatment. Findings indicate that S. indicumis well suited for use as an ecological engineering plant in the margins of rice crops. Sesame indicum can be a valuable crop as well as providing benefits to C. lividipennis whilst denying benefit to key pests.